Harnessing Artificial Intelligence to Achieve Sustainable Development Goal in Nigeria: Exploratory Notes - Ibaba, Ibaba Samuel (Kashere Journal of Politics and International Relations, 2025)
This paper is developed to answer this question. The paper explored how technological outcomes of AI can mitigate the causal factors of poverty in Nigeria , and subsequently take people out of poverty as envisaged by the SDG goal 1. The analysis revealed that if adequately harnessed, AI has the potential to serve as a catalyst that could bring Nigeria closer to achieving SDG 1. But it highlighted its limitations in dealing with antisocial, cultural, value and religious issues that also underpin the causes of poverty is in the country; in addition to challenges of implementation such as the inadequate ICT infrastructure in the country, disruptions in energy supply, low ICT literacy rate, low investments in ICT, privacy and ethical breaches concerns. The paper ended by making suggestions to mitigate the challenges